1999
DOI: 10.1182/blood.v93.3.906
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Common Polymorphism in the Factor XIII Gene With Venous Thrombosis

Abstract: We have shown an association between a common mutation in the factor XIII a-subunit gene, coding for an amino acid change, 3 amino acids from the thrombin activation site (factor XIII Val34Leu) that may protect against myocardial infarction and predisposes to intracranial hemorrhage. To investigate the possible role of factor XIII Val34Leu in the pathogenesis of venous thromboembolism (VTE) and potential interactions with factor V Leiden (FV:Q506) and prothrombin G → A 20210, we studied 221 patients with a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(27 citation statements)
references
References 6 publications
4
21
0
Order By: Relevance
“…It is now well demonstrated that the FXIII V34L polymorphism associates with FXIII speci®c transglutaminase activity, due to the thrombin-activation rate of FXIII (3, 18±22). Paradoxically, the less frequent Leu 34 allele has been identi®ed as a protective genetic factor against coronary artery disease (4, 5) and venous thrombosis (6,7 ). Also, a preliminary study indicated a slightly higher incidence of the FXIII Leu 34 variant in 62 patients with primary intracerebral haemorrhage compared with controls (23).…”
Section: Discussionmentioning
confidence: 99%
“…It is now well demonstrated that the FXIII V34L polymorphism associates with FXIII speci®c transglutaminase activity, due to the thrombin-activation rate of FXIII (3, 18±22). Paradoxically, the less frequent Leu 34 allele has been identi®ed as a protective genetic factor against coronary artery disease (4, 5) and venous thrombosis (6,7 ). Also, a preliminary study indicated a slightly higher incidence of the FXIII Leu 34 variant in 62 patients with primary intracerebral haemorrhage compared with controls (23).…”
Section: Discussionmentioning
confidence: 99%
“…To take into account the association strengths between the selected SNPs and VTE, we created a weighted GRS for each of the panels described ( Table 1). The weights assigned to each SNP were defined a priori and based on the results of published meta-analyses in the case of FVL 23 and PT 24 or data from individual reports for rs2232698, 13,25 rs1801020, 20,26,27 rs59852, 8,28,29 rs2289252, 30,31 and rs2036914 31,32 or meta-GWAS for the variants rs2066865, 19,33,34 AB0, 35 rs121909548, 14 and rs710446 36 (Tables S1 and S2). For FV Cambridge and Hong Kong, the same weights as FV Leiden were assigned.…”
Section: Genetic Risk Scorementioning
confidence: 99%
“…8 Findings on the role of this polymorphism in thrombosis risk have been inconsistent; however, both independent studies and meta-analyses suggest the 34Leu variant offers modest but significant protection against venous thrombosis. [9][10][11][12][13][14] Discovery that the effects of the Val34Leu polymorphism are mediated by gene-environment interactions between FXIII-A genotype and plasma fibrinogen concentration has resolved some of the discord. 15 For example, in the Leiden Thrombophilia Study, although Leu homozygosity showed weak protection against venous thrombosis in men, 16 reanalysis adjusting for fibrinogen concentration strengthened the association for both men and women, especially in individuals older than 45 years.…”
Section: Introductionmentioning
confidence: 99%
“…27 By extension, one might speculate that individuals with the 34Leu variant and accelerated FXIII activation would produce larger clots carrying increased venous thrombosis risk. However, the paradoxical association of the 34Leu variant with decreased venous thrombosis risk [11][12][13][14] warrants an explicit analysis of the interaction between this polymorphism and fibrinogen concentration during whole blood clot formation. Determining the impact of the 34Leu variant on clot characteristics is essential for understanding the clinical significance of the FXIII-A Val34Leu polymorphism in thrombosis risk.…”
Section: Introductionmentioning
confidence: 99%